2013
DOI: 10.3348/kjr.2013.14.5.781
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Features in an Adult Pancreatic Hemangioma: CT and MRI Demonstration

Abstract: Hemangiomas in the pancreas are very rare and only a few cases in adulthood have been reported in the literature. We describe a case of pancreatic hemangiomas in an adult with unique imaging findings. A 23-year-old woman visited the hospital for an incidentally detected pancreatic mass. CT and MRI revealed a multilocular cyst with fluid-fluid levels and no obvious enhancement. The patient underwent surgery and the mass was confirmed as a pancreatic hemangioma. The radiological features and differential diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
0
18
1
3
Order By: Relevance
“…This is explained by the slow blood flow due to the presence of AV shunting. On MRI scan it appears as a lobulated, hypo-intense mass in T1-weighted images, and shows moderate hyperintensity signal in T2-weighted image [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is explained by the slow blood flow due to the presence of AV shunting. On MRI scan it appears as a lobulated, hypo-intense mass in T1-weighted images, and shows moderate hyperintensity signal in T2-weighted image [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, patients are strictly asymptomatic and abdominal imaging showed an incidental finding of pancreatic cystic lesion. Rarely, they present with pancreatitis or abnormalities in the liver function test [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid-fluid levels in tumors display a radiological appearance of two fluid levels in the cystic section of tumors (4)(5)(6)(7)(8)(9)(10). This level is apparent on computed tomography (CT) and magnetic resonance imaging (MRI) scans, particularly on T2-weighted MRI scans (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This level is apparent on computed tomography (CT) and magnetic resonance imaging (MRI) scans, particularly on T2-weighted MRI scans (4)(5)(6)(7)(8)(9)(10)(11). Previous studies have reported fluid-fluid levels in non-neurogenic tumors (4,5), as well as a small number of cranial nerve schwannomas, including trigeminal, glossopharyngeal and hypoglossal schwannomas (6)(7)(8). However, cystic VSs with fluid-fluid levels are fairly rare (3,6,9,10).…”
Section: Introductionmentioning
confidence: 99%